Educación y calidad de vida: una mirada en relación a la construcción de la subjetividad femenina - Vinces Salazar, Fabián (2012)
The present article examines the relationship amongeducation and development of women, highlightingthe psychological variables of self-determinationand quality of life. Additionally, proposes anunderstanding of the process of construction offemale subjectivity currently from the psychologicaland social perspective.